Housing Purchases and Transitory Income: A Study with Panel Data - Dynarski, Mark; Sheffrin, Steven M. (The Review of Economics and Statistics, 1985)
In this paper we explore the role of transitory income in the housing purchase decision. Because of moral hazard considerations banks typically require downpayments to be financed internally, hence transitory income is potentially important in overcoming the downpayment constraint. Using a novel approach to the measurement of permanent and transitory income, we estimate a two-stage model in which households decide whether to purchase housing in the first stage and the quantity to be purchased in the second. The results indicate a significant role for transitory income in both decision stages.